Lethal agent [compact disc, unabridged] : a Mitch Rapp novel - Mills, Kyle, 1966-; Flynn, Vince, 1966-2013 (Flynn, Vince, 1966-2013. Mitch Rapp novel., 2019)
A divisive presidential election is complicated by terrorist videos of a kidnapped scientist who is being forced to produce anthrax, catapulting Mitch Rapp into an undercover mission to prevent the weapon from being smuggled into America.